Methylation specific-high resolution melting analysis of DISC1 - Abd. Rahim, Nour El Huda; Ku Zaifah, Norsidah; A.Talib, Norlelawati (2014)

(untitled)
Introduction: The evidence of Disrupted in Schizophrenia 1 (DISC1) gene’s role in schizophrenia came through functional and animal studies. However the exact genetic basis that contribute to the role is still not established. As meta-analyses findings have denied DISC1 variants as the genetic basis, emphasis is now shifted to genetic defect such as copy number and epigenetic which have not been well explored. Objectives: We aim to explore the epigenetic dysregulation as the basis of DISC1 gene contribution to schizophrenia. To achieve this aim, method for quantitation of DISC1’s DNA methylation has to be established. Methods: The high resolution melting (HRM) analysis method was adopted for DNA methylation assay. Primers were designed based on Wojdacz’s protocol with some modifications. The human methylated and unmethylated control DNA samples were titrated into serial methylation percentage of 0%, 25%, 50%, 75% and 100% and were bisulfite treated. The methylation specific-high resolution melting (MS-HRM) assay for DISC1 was optimized based on its response to various percentage of DNA methylation. Results: The optimized protocol clearly demonstrated the serial methylated percentage differentiation of 0%, 25%, 50%, 75% and 100% accordingly. Conclusion: This optimized HRM protocol is to be used for the actual MS-HRM analysis of the DISC1 in schizophrenia.